2018
DOI: 10.33151/ajp.15.1.548
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the potential of iPads to actively engage paramedicine students in an authentic learning experience

Abstract: IntroductionParamedicine students are required to develop the skills of assessing and managing clinical presentations to prepare them for practice. Active learning strategies that are student centred, facilitate collaboration and mirror workplace practices can assist the development of requisite skills. iPads provide a portable means of integrating audiovisual material into these clinical scenarios. Use of such material has the potential to add a degree of authenticity to this environment and require s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Although clinical improvements and technological advancements have seen a rapid shift in paramedic practice in Australia since the early 2000s, deficiencies in the ability to perform basic drug calculations among both qualified and student paramedics and nurses has been documented (6)(7)(8)(9). Critical interventions such as advanced airway support, increased pharmacology and prescribing are examples of the evolving role of the paramedic (16)(17)(18). Coupled with the dynamic encounters and clinical challenges of the environment that paramedics operate within, the abilities of the attending paramedics to perform basic calculations are principle to best practice (2,7,8).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although clinical improvements and technological advancements have seen a rapid shift in paramedic practice in Australia since the early 2000s, deficiencies in the ability to perform basic drug calculations among both qualified and student paramedics and nurses has been documented (6)(7)(8)(9). Critical interventions such as advanced airway support, increased pharmacology and prescribing are examples of the evolving role of the paramedic (16)(17)(18). Coupled with the dynamic encounters and clinical challenges of the environment that paramedics operate within, the abilities of the attending paramedics to perform basic calculations are principle to best practice (2,7,8).…”
Section: Discussionmentioning
confidence: 99%
“…Strategies to reduce errors in drug administration have evolved within paramedic care (16)(17)(18). Bernius et al found that the use of a paediatric code card in drug calculations improved the calculation ability of paramedics from 65%, for those who did not use the card to 94% for those that did (11).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even though tablets are the latest tool for learning, there are some serious gaps in this area of research that need to be addressed, such as how well students are using tablets in the classroom and whether tablets can increase students' motivation, engagement, and participation. Such investigations have been done in developed countries such as Canada (Karsenti & Fievez, 2013), Australia, (Clarkson, 2018), and the United States (Chou, Block, & Jesness, 2012Mango, 2015;Shen, 2016). However, very little research has been done in developing countries like South Africa.…”
Section: Chris Merrillmentioning
confidence: 99%